2019
DOI: 10.1038/s41598-019-56619-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-protozoal activity of extracts from chicory (Cichorium intybus) against Cryptosporidium parvum in cell culture

Abstract: Cryptosporidium spp. are responsible for severe public health problems and livestock production losses. Treatment options are limited to only one drug available for human and bovine cryptosporidiosis, respectively, and both drugs exhibit only partial efficacy. Sesquiterpene lactones (SL) are plant bioactive compounds that function as a defence mechanism against herbivores. SL have demonstrated anti-parasitic properties against a range of parasitic taxa but knowledge about their anti-Cryptosporidium efficacy is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Woolsey et al demonstrated the efficacy of chicory leaf and root extracts against Cryptosporidium parvum , with the lower SL extract (leaf) showing greater inhibition. Based on the results, the authors suggest that the antiparasitic activity does not appear to be related only to the SL content [ 45 ]. Marley et al conducted a study on lambs that acquired parasites by natural transmission.…”
Section: Health-promoting Propertiesmentioning
confidence: 99%
“…Woolsey et al demonstrated the efficacy of chicory leaf and root extracts against Cryptosporidium parvum , with the lower SL extract (leaf) showing greater inhibition. Based on the results, the authors suggest that the antiparasitic activity does not appear to be related only to the SL content [ 45 ]. Marley et al conducted a study on lambs that acquired parasites by natural transmission.…”
Section: Health-promoting Propertiesmentioning
confidence: 99%
“…As such, we allowed 2 h for the establishment of infection in this study. Furthermore, the 2–4 h time point has been used by many research groups (including ours) in the recent past to assess the in vitro effect of compounds on these parasites before and after invasion of host cells ( Jumani et al, 2019 ; Woolsey et al, 2019 ; Funkhouser-Jones et al, 2020 ; Li et al, 2020 ; Ma et al, 2020 ; Murakoshi et al, 2020 ). When the cultures were analyzed at 72 h post-infection, five compounds (JS-2-22, 27, 28, 30 and 44) were found to have concentration-dependent activity of reducing C. parvum growth and proliferation, regardless of whether treatment started immediately or 2 h after infection of host cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a hepatoprotective agent, it also decreases the threat of liver cirrhosis [6]. Other pharmacological application of chicory includes antihypoglycemic, antihyperlipidemic [90,91], anticancer [92], anti-allergic [93], anti-ulcerogenic [94], gastroprotective [95], anti-protozoal [96], and wound healing activities [23]. It has evaluated to be an anti-hyperuricemia agent [97], and also depicted anti-rheumatic effects [98].…”
Section: Medicinal Values Of Cichorium Intybusmentioning
confidence: 99%